A novel gene mutation in the 60s loop of human coagulation factor VII – inhibition of interdomain crosstalk - Kavlie, Anita; Wiiger, Merete Thune; Husbyn, Mette; Stormorken, Helge; Prydz, Hans (Thrombosis and Haemostasis, 2004)
A novel mutation in the factor VII gene resulting in procoagulant activity of 7.5% and antigen levels of 23% is presented. Single-stranded conformational polymorphism and DNA sequencing analysis revealed heterozygous shifts, and mutations were detected in exons 5, 7 and 8. The mutant L204P in exon 7 was novel, while the common polymorphisms, H115H and R353Q, were located in exons 5 and 8, respectively.The molecular effect of the L204P mutation was characterized using recombinant mammalian expression in Chinese hamster ovary cells. Low levels (4 ng/ml) of secreted mutant protein were found in transiently transfected cells compared to wild-type factor VII (83 ng/ml). Metabolic labeling demonstrated that the rate of mutant protein synthesis was similar to that of wild-type FVII, and the mutant protein accumulated intracellularly with no signs of increased degradation during a four-hour chase. No interaction between secreted P204 protein and immobilized soluble tissue factor was detected using surface plasmon resonance. The activation rate of recombinant mutant FVII protein was strongly reduced compared to wild-type FVII. A 9-fold reduction in the rate of FX activation was detected whereas Km was nearly the same for wild-type and the mutant. This slow rate was caused by a correspondingly lowered rate of P204 activation. A synthetic peptide sequence comprising amino acids 177−206 blocked binding of FVIIa to the TF-chip, and the subsequent factor X activation with an IC50 value of 0.5 μM in a chromogenic factor Xa assay. Additionally, evaluation of the peptide by surface plasmon resonance analysis resulted in inhibition of complex formation with an apparent Ki of 7 μM.
Keywords: Activation loop; congenital coagulation defect; reduced factor VII activation; absence of TF/FVII complex; 60s loop